Understanding tuberculosis and its control anthropological and ethnographic approaches - MacDonald, Helen; Harper, Ian (Routledge, an imprint of the Taylor & Francis Group, 2020)
Over the last two decades, attempts to control the problem of tuberculosis have become increasingly more complex, as countries adopt and adapt to evolving global TB strategies. Significant funding has also increased apace, diagnostic possibilities have evolved, and greater attention is being paid to developing broader health systems. Against this background, this book examines tuberculosis control through an anthropological lens. Drawing on ethnographic case studies from China, India, Nepal, South Africa, Romania, Brazil, Ghana and France, the volume considers: the relationship between global and national policies and their unintended effects; the emergence and impact of introducing new diagnostics; the reliance on and use of statistical numbers for representing tuberculosis, and the politics of this; the impact of the disease on health workers, as well as patients; the rise of drug-resistant forms; and issues of attempted control. Together, the examples showcase the value of an anthropological understanding to demonstrate the broader bio-political and social dimensions of tuberculosis and attempts to deal with it